Avaliação da hibridização do esmalte dentário através de fluxo eletrocinético - Maciel, Patricia Pereira (2014)
The transport of materials through the tooth enamel is conventionally derived from the diffusion process, which leads to a number of limitations, because the pores of the enamel are extremely small, requiring a certain extension, as occurs in adhesive techniques by the etching process. An alternative method to this technique is the electrokinetic flow (EKF), which promotes the unidirectional flow of substances through the pores of the enamel by applying an external electric field. Based on this premise it was promoted the infiltration of a composite resin with low viscosity (Icon DMG, Hamburg, Germany) on the surface of 20 extracted human teeth by EKF, using an electric field (1.5V) in two stages: (1) infiltration of potassium chloride 0.1M (KCl) during 3h and (2) infiltration of the resin during 2h. Longitudinal histological sections of ≈ 100μm were analyzed by fluorescence microscopy and polarized light microscopy associated with the "polscopesingle"system, after 24h of dehydration and along 50, 100, 150, 200, 250, 300, 350, 400, 450 and 500μm deep. Electric voltage (μA) presented to be positive during infiltration. Images from Fluorescence Microscopy revealed fluorescence of the infiltrated enamel areas for all samples, from the surface to the dentin-enamel junction (DEJ), indicating the formation of a hybrid layer with average depth of 1627.66 μm and a standard deviation of 284.20 μm. The records of the phase delay during dehydration of the infiltrated and non-infiltrated areas did not present changes in the infiltrated area. It was observed that the water was replaced by the resin (p<0.000001), with high effect size (>0.8). Based on these results, it was concluded that the EKF resulted in infiltration of the resin into the enamel nanochannels.